1st Central European Congress on Intensive Care Medicine - Cerny, Vladimir; Marek, Oldrich (Biomedical papers, 2002)
This issue of Biomedical Papers (Vol. 146, No 1) contains abstracts of the scientific papers to be presented at the 1st Central European Congress on Intensive Care Medicine.1 The abstracts appear in order of presentation from Thursday 13 through Saturday 15 June 2002. This abstract book would have been impossible to produce without the help of several people from organizing and scientific committee, special thanks must be given to the Editorial Board of Biomed. Papers, which provided immense help toward successful completion of accepted papers. Our thanks also must go to people from Publishing Centre of Palacky University.On behalf of Organizing and Scientific Committee of 1st Central European Congress on Intensive Care Medicine we wish you a pleasant stay at Olomouc.
Keywords: abstracts of the scientific papers